Sobre soluções para equações de Schrödinger quaselineares generalizada com crescimento crítico - Germano, Diogo de Santana (2020)
In this work, we study questions related to the existence, non-existence and concentration behavior of stationary wave solutions for a class of Generalized Quaselinear Schrödinger Equations with critical growth, such as which model physical elements, such as ﬂuid mechanics, plasmas and dissipative quantum mechanics. In obtaining our results, we used a Pohozaev identity, ﬁxed point theory in ordered spaces and variational methods, such as mini-max theorems.